Electrolytic capacitor and method for manufacturing the same
By placing hydroxyl-containing compounds in the capacitor element precursor and forming a conductive polymer layer, the shortcomings in the existing electrolytic capacitors in terms of voltage resistance and reliability are solved, and the manufacturing of high-characteristic electrolytic capacitors and efficient electrolyte layer stability are achieved.
Patent Information
- Application Number
- CN202180011047.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Existing electrolytic capacitors have shortcomings in high voltage withstandability and reliability, and it is difficult to meet high characteristics requirements.
By placing the hydroxyl-containing compound inside the precursor of the capacitor element and forming a conductive polymer layer thereon, the stability and electrical conductivity of the electrolyte layer are improved.
The manufacturing of high-characteristic electrolytic capacitors is realized, the breakdown voltage and reliability of the capacitor are improved, and the equivalent series resistance (ESR) value is reduced.
Smart Images

Figure CN115023779B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing the same. Background Art
[0002] Capacitors used in electronic devices are required to have large capacitance and a low equivalent series resistance (ESR) in the high frequency region. As capacitors with large capacitance and low ESR, electrolytic capacitors using conductive polymers such as polypyrrole, polythiophene, polyfuran, and polyaniline are promising. Patent document 1 discloses a method of impregnating a dispersion containing a conductive polymer and a solvent to form a capacitor element by winding an anode foil and a cathode foil with a separator interposed therebetween.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2008-10657 Summary of the invention
[0006] Problems to be solved by the invention
[0007] Currently, electrolytic capacitors with higher characteristics (especially high withstand voltage and high reliability) are desired. Under such circumstances, one of the objects of the present invention is to provide an electrolytic capacitor with high characteristics and a method for manufacturing the same.
[0008] Means for solving problems
[0009] One aspect of the present invention relates to a method for manufacturing an electrolytic capacitor. The manufacturing method is a method for manufacturing an electrolytic capacitor comprising a foil-shaped anode body having a dielectric layer on the surface and a foil-shaped cathode body, and comprises: step (i), forming a capacitor element precursor by winding or stacking a separator and the anode body and the cathode body facing each other with the separator sandwiched therebetween; step (ii), placing a hydroxyl-containing compound having a melting point of 50°C or above, which is at least one compound selected from a group consisting of sugars and polyols, inside the capacitor element precursor; and step (iii), forming a conductive polymer layer containing a conductive polymer inside the capacitor element precursor after step (ii), wherein step (ii) comprises: step (ii-a), impregnating the capacitor element with an aqueous treatment liquid containing the hydroxyl-containing compound; precursor; and step (ii-b), configuring the hydroxyl-containing compound inside the capacitor element precursor by drying the impregnated aqueous treatment liquid, the step (iii) comprising: step (iii-a), impregnating the capacitor element precursor that has undergone the step (ii) with an aqueous dispersion containing the conductive polymer; and step (iii-b), forming the conductive polymer layer by drying the impregnated aqueous dispersion, the drying in the step (ii-b) being performed at a prescribed temperature, the prescribed temperature being a temperature above the boiling point of the aqueous treatment liquid under the pressure at which the drying in the step (ii-b) is performed and being a temperature below the melting point of the hydroxyl-containing compound under the pressure at which the drying in the step (ii-b) is performed.
[0010] Another aspect of the present invention relates to a method for manufacturing an electrolytic capacitor. The manufacturing method is a method for manufacturing an electrolytic capacitor comprising a porous anode body having a dielectric layer on the surface, comprising: step (I), disposing a hydroxyl-containing compound having a melting point of 50°C or above, which is at least one compound selected from a group consisting of sugars and polyols, on the surface of the anode body; and step (II), forming a conductive polymer layer containing a conductive polymer on the anode body that has undergone step (I), wherein step (I) comprises: step (Ia), impregnating the anode body with an aqueous treatment liquid containing the hydroxyl-containing compound; and step (Ib), drying the impregnated aqueous treatment liquid to remove the conductive polymer. A hydroxyl-containing compound is arranged on the surface of the anode body, and the step (II) comprises: a step (II-a) of impregnating the anode body that has undergone the step (I) with an aqueous dispersion containing a conductive polymer; and a step (II-b) of forming the conductive polymer layer on the anode body by drying the impregnated aqueous dispersion, wherein the drying in the step (Ib) is carried out at a prescribed temperature, which is a temperature above the boiling point of the aqueous treatment liquid under the pressure of the drying in the step (Ib) and a temperature below the melting point of the hydroxyl-containing compound under the pressure of the drying in the step (Ib).
[0011] Another aspect of the present invention relates to an electrolytic capacitor. The electrolytic capacitor is an electrolytic capacitor including a capacitor element, the capacitor element including an electrode group and an electrolyte layer in contact with the anode body, the cathode body and the separator, the electrode group including a foil-shaped anode body having a dielectric layer on the surface, a foil-shaped cathode body and a separator, the electrode group is a wound body formed by winding the anode body and the cathode body facing each other with the separator sandwiched therebetween, or a stacked body formed by stacking the anode body and the cathode body facing each other with the separator sandwiched therebetween, the electrolyte layer containing a conductive polymer and a hydroxyl-containing compound having a melting point of 50° C. or more, which is at least one compound selected from the group consisting of sugars and polyols, and the hydroxyl-containing compound is unevenly distributed in the peripheral portion of the capacitor element compared to the central portion of the capacitor element.
[0012] Another aspect of the present invention relates to an electrolytic capacitor. The electrolytic capacitor is an electrolytic capacitor including a capacitor element, the capacitor element including a porous anode body having a dielectric layer on the surface, a cathode layer, and an electrolyte layer arranged between the anode body and the cathode layer, the capacitor element containing a conductive polymer and a hydroxyl-containing compound having a melting point of 50° C. or higher, which is at least one compound selected from the group consisting of sugars and polyols, and the hydroxyl-containing compound is concentrated in the peripheral portion of the anode body rather than the central portion of the anode body.
[0013] Effects of the Invention
[0014] According to the present invention, an electrolytic capacitor with high characteristics can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a cross-sectional view schematically showing an example of the electrolytic capacitor of the present invention.
[0016] Figure 2 It is schematically indicated Figure 1 A diagram of a portion of an electrolytic capacitor is shown.
[0017] Figure 3 It is a cross-sectional view schematically showing a part of another example of the electrolytic capacitor of the present invention.
[0018] Figure 4 It is a figure which shows the result of Example. DETAILED DESCRIPTION
[0019] Hereinafter, the embodiments of the present invention will be described by way of example, but the present invention is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes exemplified, but other numerical values and materials may also be applied as long as the effects of the present invention can be obtained. It should be noted that in the following description, unless otherwise specified, the melting point is the value under 1 atmosphere. In addition, unless otherwise specified, the viscosity is the value at room temperature (25° C.) and 1 atmosphere.
[0020] As a result of the research, the inventors of the present application have found that an electrolytic capacitor having high characteristics can be obtained by placing a conductive polymer in a capacitor element precursor by a specific method. The present invention is based on this new finding.
[0021] The electrolytic capacitor of the present invention may be the first electrolytic capacitor described below or the second electrolytic capacitor described below. These are described below.
[0022] [No. 1 electrolytic capacitor]
[0023] The first electrolytic capacitor is an electrolytic capacitor comprising a capacitor element. The capacitor element comprises an electrode group and an electrolyte layer in contact with an anode body, a cathode body and a separator, wherein the electrode group comprises a foil-shaped anode body having a dielectric layer on the surface, a foil-shaped cathode body and a separator. The electrode group may be a wound body formed by winding the anode body, the cathode body and the separator in a manner that a separator is arranged between the anode body and the cathode body. Alternatively, the electrode group may also be a laminate formed by folding the anode body, the cathode body and the separator into a zigzag shape in a manner that a separator is arranged between the anode body and the cathode body. The electrolyte layer contains a conductive polymer and a hydroxyl-containing compound having a melting point of 50°C or more, which is at least one compound selected from a group consisting of sugars and polyols. The hydroxyl-containing compound is sometimes referred to as "hydroxyl-containing compound (C)" hereinafter. For the hydroxyl-containing compound (C), it is biased towards the peripheral portion of the capacitor element compared to the central portion of the capacitor element.
[0024] The electrolyte layer of the first electrolytic capacitor includes a hydroxyl-containing compound (C). The hydroxyl-containing compound (C) improves the fixability of the conductive polymer by utilizing its hydroxyl group. As a result, good properties (especially low ESR) can be achieved. Since the stability of the electrolyte layer is enhanced due to the improvement of the fixability of the conductive polymer, the reliability of the electrolytic capacitor can be improved.
[0025] The peripheral portion of the capacitor element is prone to defects in the dielectric layer (oxide film) of the anode body. By arranging the hydroxyl-containing compound (C) having multiple hydroxyl groups in this portion, it is easy to repair the defects of the dielectric layer. As a result, a highly reliable electrolytic capacitor can be obtained. Specifically, an electrolytic capacitor with a high breakdown voltage and not prone to short circuit can be obtained.
[0026] Furthermore, by localizing the hydroxyl group-containing compound (C) in the peripheral portion of the capacitor element, the conductive polymer can be localized in the peripheral portion. That is, the conductive polymer layer in the peripheral portion can be formed thickly.
[0027] The electrode group of the first electrolytic capacitor is not particularly limited, and a known electrode group can be used. For example, in the electrode group as a winding body, an electrode group used in a general winding electrolytic capacitor can be used. Similarly, in the electrode group as a stack, an electrode group used in a general stacked electrolytic capacitor can be used. For example, the electrode group as a stack includes an electrode group in which a foil-like anode body, a foil-like cathode body, and a separator are overlapped and folded into a zigzag shape, thereby stacking them. At this time, they are configured in a manner in which a separator is present between the foil-like anode body and the foil-like cathode body. Examples of foil-like anode bodies, foil-like cathode bodies, and separators will be described later.
[0028] (Hydroxy-containing compound (C))
[0029] The hydroxyl-containing compound (C) contained in the electrolyte layer of the first electrolytic capacitor is described as follows. The hydroxyl-containing compound (C) is at least one compound selected from the group consisting of sugars and polyols, and has a melting point of 50°C or more. The melting point of the hydroxyl-containing compound (C) is preferably higher than the temperature at which the capacitor is used. The melting point of the hydroxyl-containing compound (C) may be in the range of 80°C to 300°C (e.g., in the range of 120°C to 300°C).
[0030] Examples of sugars include glucose, etc. Examples of polyols include mannitol, sorbitol, xylitol, pentaerythritol, trimethylolpropane, etc. It should be noted that mannitol, sorbitol, xylitol, pentaerythritol, etc. are sometimes referred to as sugar alcohols. The hydroxyl-containing compound may also be a sugar alcohol.
[0031] The number of hydroxyl groups contained in the hydroxyl group-containing compound (C) may be in the range of 2 to 12 (eg, in the range of 3 to 6). Usually, the hydroxyl group-containing compound (C) is a water-soluble compound.
[0032] From another point of view, the following organic compound can be used as the hydroxyl-containing compound contained in the electrolyte layer of the first electrolytic capacitor, that is, the organic compound (e.g., an organic compound that is not a polymer) contains a plurality of hydroxyl groups (-OH) bonded to carbon atoms and has a melting point within the above range. The molecular weight of the organic compound and the number of hydroxyl groups contained in the organic compound can each be within the above range exemplified for the hydroxyl-containing compound.
[0033] The hydroxyl-containing compound (C) may be at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol and trimethylolpropane. The melting point of glucose is about 146-150°C, the melting point of mannitol is about 165-169°C, the melting point of sorbitol is about 93-95°C, the melting point of xylitol is about 92-97°C, the melting point of pentaerythritol is about 257-260°C, and the melting point of trimethylolpropane is about 56-58°C. It should be noted that these substances sometimes fluctuate in melting point due to differences in structure (stereoisomers). Glucose, mannitol and pentaerythritol are preferred from the perspective of high melting point.
[0034] (Conductive polymer)
[0035] The conductive polymer (conductive polymer) used in the first electrolytic capacitor is described as follows. Examples of conductive polymers include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene and their derivatives. The derivatives include polymers with polypyrrole, polythiophene, polyfuran, polyaniline and polyacetylene as basic skeletons. For example, polythiophene derivatives include poly(3,4-ethylenedioxythiophene) and the like. These conductive polymers can be used alone or in combination. In addition, the conductive polymer can also be a copolymer of two or more monomers. The weight average molecular weight of the conductive polymer is not particularly limited, for example, it can be in the range of 1000 to 100000. A preferred example of a conductive polymer is poly(3,4-ethylenedioxythiophene) (PEDOT).
[0036] Dopants can be added to the conductive polymer. From the viewpoint of suppressing dedoping from the conductive polymer, it is preferred to use a polymer dopant. Examples of polymer dopants include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly (2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, etc. They can be used alone or in combination of two or more. They can be added in the form of a salt. The polymer dopant can exist in the electrolyte in the form of anions in which cations (such as protons) are dissociated from at least a portion of the acidic group. A preferred example of a dopant is polystyrene sulfonic acid (PSS).
[0037] The weight average molecular weight of the dopant is not particularly limited, but can be in the range of 1,000 to 100,000 from the viewpoint of facilitating the formation of a uniform electrolyte layer.
[0038] The conductive polymer may be poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonic acid.
[0039] The electrode group of the first electrolytic capacitor may be a wound body. In this case, the electrolyte layer preferably has a biased portion with a hydroxyl-containing compound at both ends of the winding axis direction of the winding body and the outermost peripheral portion of the winding body. Defects of the dielectric layer (oxide film) of the anode body are easily generated at both ends of the winding axis direction of the winding body and the outermost peripheral portion of the winding body. By biasing the hydroxyl-containing compound (C) to these parts, the repair of defects in the dielectric layer can be promoted.
[0040] The anode body and cathode body of the first electrolytic capacitor generally have a rectangular plan view shape. In this case, the vicinity of both end portions of the wound body in the winding axis direction can be regarded as the vicinity of the long sides of the rectangular anode body and cathode body.
[0041] The electrode group of the first electrolytic capacitor may also be a laminate. In this case, the electrolyte layer has a portion where the hydroxyl-containing compound is biased in the portion in contact with the peripheral portion of the anode body. Since the peripheral portion of the anode body is prone to defects in the dielectric layer (oxide film) of the anode body, it is preferred that the hydroxyl-containing compound (C) is biased in these portions.
[0042] The electrolyte layer of the first electrolytic capacitor may contain a non-aqueous solvent or a non-aqueous electrolyte. Hereinafter, the non-aqueous solvent and the non-aqueous electrolyte contained in the electrolyte layer are sometimes collectively referred to as "liquid component (L)". The liquid component (L) may be a substance that is liquid at room temperature (25°C) or a substance that is liquid at the temperature when the first electrolytic capacitor is used. A preferred example of the liquid component (L) is a liquid that does not substantially dissolve the hydroxyl-containing compound (C).
[0043] The non-aqueous solvent may be an organic solvent or an ionic liquid. Examples of the non-aqueous solvent include polyols such as ethylene glycol and propylene glycol, cyclic sulfones such as sulfolane (SL), lactones such as γ-butyrolactone (γBL), amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, carbonate compounds such as propylene carbonate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, formaldehyde, and the like.
[0044] In addition, polymer solvents can also be used as non-aqueous solvents. In the example of polymer solvents, at least one of the hydroxyl groups in polyalkylene glycol, polyalkylene glycol derivatives, and polyols is substituted with polyalkylene glycol (including derivatives) compounds, etc. are included. Specifically, in the example of polymer solvents, polyethylene glycol (PEG), polyethylene glycol glyceryl ether, polyethylene glycol diglyceryl ether, polyethylene glycol sorbitol ether, polypropylene glycol, polypropylene glycol glyceryl ether, polypropylene glycol diglyceryl ether, polypropylene glycol sorbitol ether, polybutylene glycol, etc. are included. In the example of polymer solvents, copolymers of ethylene glycol-propylene glycol, copolymers of ethylene glycol-butylene glycol, copolymers of propylene glycol-butylene glycol, etc. are also included. Non-aqueous solvents can be used alone or in combination of two or more.
[0045] Liquid component (L) can contain acid component and alkali component. In the example of acid component, include maleic acid, phthalic acid, benzoic acid, pyromellitic acid, resorcinic acid (resorcinic acid) etc. In the example of alkali component, include 1,8-diazabicyclo [5,4,0] undecyl-7-ene, 1,5-diazabicyclo [4,3,0] non-5-ene, 1,2-dimethyl imidazolinium, 1,2,4-trimethyl imidazoline, 1-methyl-2-ethyl-imidazoline, 1,4-dimethyl-2-ethyl imidazoline, 1-methyl-2-heptyl imidazoline, 1-methyl-2-(3'heptyl) imidazoline, 1-methyl-2-dodecyl imidazoline, 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine, 1-methylimidazole, 1-methylbenzimidazole etc.
[0046] The non-aqueous electrolyte comprises a non-aqueous solvent and a solute (e.g., an organic salt) dissolved therein. Examples of non-aqueous solvents forming non-aqueous electrolytes include the above-mentioned examples of non-aqueous solvents. Examples of solutes include inorganic salts and organic salts. The so-called organic salt is a salt in which at least one of the anions and cations contains an organic substance. Examples of organic salts include trimethylamine maleate, triethylamine boron disalicylate, ethyldimethylamine phthalate, 1,2,3,4-tetramethylimidazolinium phthalate, and 1,3-dimethyl-2-ethylimidazolinium phthalate.
[0047] In order to suppress dedoping of the dopant, the pH of the liquid component (L) may be set to less than 7, or may be set to 5 or less.
[0048] (Anode)
[0049] A metal foil having a dielectric layer formed on the surface can be used as the anode body. The type of metal forming the metal foil is not particularly limited. From the aspect of facilitating the formation of the dielectric layer, examples of the metal forming the metal foil include valve metals such as aluminum, tantalum, niobium, titanium, and alloys of valve metals. A preferred example is aluminum and aluminum alloys. Usually, the surface of the anode body is roughened, and the dielectric layer is formed on the roughened surface. The electrolyte layer is in contact with the dielectric layer of the anode body.
[0050] (Cathode)
[0051] Metal foil can be used as the cathode body. The type of metal forming the metal foil is not particularly limited. Examples of metals forming the metal foil include valve metals such as aluminum, tantalum, niobium, titanium, and alloys of valve metals. A preferred example is aluminum and aluminum alloys. In addition, a chemically generated coating film can be provided on the surface of the cathode body, and a coating of a metal (dissimilar metal) or a non-metallic film different from the metal forming the cathode body can also be provided. Examples of dissimilar metals and non-metals include metals such as titanium and non-metals such as carbon.
[0052] (Spacer)
[0053] As the spacer, a sheet-like object that can be impregnated with an electrolyte can be used. For example, a sheet-like object that has insulation and can be impregnated with an electrolyte can be used. The spacer can be a woven fabric, a non-woven fabric, or a porous film. Examples of materials for the spacer include cellulose, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, vinylon, nylon, aromatic polyamide, polyimide, polyamide-imide, polyetherimide, rayon, and glass.
[0054] The electrolyte of the electrolytic capacitor of the present invention contains a hydroxyl-containing compound (C). The hydroxyl-containing compound (C) can be used to improve the strength of the spacer. In previous electrolytic capacitors, if a weak spacer (for example, a spacer formed of cellulose-based natural fibers such as Manila hemp and spicate) is used, the characteristics of the capacitor such as the withstand voltage are reduced. By using a hydroxyl-containing compound (C), the reduction of such characteristics can be suppressed. It should be noted that the effect of strengthening the spacer can be obtained regardless of the type of the spacer.
[0055] [Second electrolytic capacitor]
[0056] The second electrolytic capacitor is an electrolytic capacitor including a capacitor element. The capacitor element includes a porous anode body having a dielectric layer on the surface, a cathode layer, and an electrolyte layer disposed between the anode body and the cathode layer. The capacitor element contains a conductive polymer and a hydroxyl-containing compound having a melting point of 50°C or above, which is at least one compound selected from a group consisting of sugars and polyols. For the hydroxyl-containing compound, it is biased towards the peripheral portion of the anode body compared to the central portion of the anode body. The compounds exemplified for the hydroxyl-containing compound of the first electrolytic capacitor can be used as the hydroxyl-containing compound used in the second electrolytic capacitor. Therefore, the above-mentioned hydroxyl-containing compound used in the second electrolytic capacitor is sometimes referred to as "hydroxyl-containing compound (C)".
[0057] The porous anode body can be columnar (e.g., cylindrical, square columnar) or plate-shaped. The porous anode body is usually a sintered body formed by sintering as described later. The peripheral portion of these porous anode bodies is prone to defects. In the second electrolytic capacitor, by arranging the hydroxyl-containing compound (C) at the peripheral portion of the porous anode body, the defects of the peripheral portion can be suppressed. Therefore, an electrolytic capacitor with high characteristics can be obtained. In addition, a hydroxyl-containing compound (C) is present at the peripheral portion of the anode body (i.e., near the interface between the electrolyte layer and the anode body of the second electrolytic capacitor). Therefore, the effect described in the first electrolytic capacitor can be obtained.
[0058] Furthermore, by localizing the hydroxyl group-containing compound (C) in the peripheral portion of the anode body, the conductive polymer can be localized in the peripheral portion. That is, the conductive polymer layer in the peripheral portion can be formed thickly.
[0059] The hydroxyl group-containing compound (C) used in the second electrolytic capacitor may be at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol, and trimethylolpropane.
[0060] The electrolyte layer of the second electrolytic capacitor may be a solid electrolyte layer. The electrolyte layer may be formed using a manganese compound or a conductive polymer. The conductive polymer described for the electrolyte layer of the first electrolytic capacitor may be used as the conductive polymer. For example, the conductive polymer may be poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid.
[0061] The electrolyte layer (e.g., solid electrolyte layer) containing a conductive polymer can be formed by polymerizing a raw material monomer on the dielectric layer of the anode body. Alternatively, it can be formed by applying a liquid containing a conductive polymer to the dielectric layer of the anode body. The electrolyte layer can be composed of one layer or two or more layers of different materials.
[0062] The anode body, cathode layer and electrolyte layer of the second electrolytic capacitor are not particularly limited except for matters related to the hydroxyl-containing compound (C). For example, the anode body, cathode layer and electrolyte layer of the second electrolytic capacitor can be formed using materials and techniques used in known electrolytic capacitors including porous anode bodies. The anode body and cathode layer of the second electrolytic capacitor are described as follows.
[0063] The porous anode body can be, for example, a porous sintered body obtained by sintering particles of a valve metal material. The anode body can be in the shape of a rectangular parallelepiped. Examples of valve metals include titanium (Ti), tantalum (Ta), niobium (Nb), etc. The material particles can also be formed by an alloy containing a valve metal. For example, an alloy containing a valve metal and silicon, vanadium, boron, etc. can also be used. The alloy of the valve metal contains the valve metal as the main component, for example, contains more than 50 atomic % of the valve metal. In addition, material particles formed by a compound containing a valve metal and a typical element such as nitrogen can also be used. The material particles can be used alone or in combination of two or more.
[0064] The anode body has a dielectric layer on its surface. Therefore, the electrolyte layer is in contact with the dielectric layer of the anode body. The dielectric layer can be formed, for example, by subjecting a sintered body to be the anode body to a chemical conversion treatment and growing an oxide film on the surface of the sintered body.
[0065] The cathode layer has a current collecting function. The cathode layer is formed, for example, of a conductive material. The cathode layer may be a conductive layer formed in a manner covering the electrolyte layer. The cathode layer may include a carbon layer formed in a manner covering the electrolyte layer and a metal paste layer formed on the carbon layer. The carbon layer may include a conductive carbon material such as graphite and a resin. The metal paste layer may include metal particles (e.g., silver particles) and a resin.
[0066] As examples of the methods of the present invention for manufacturing electrolytic capacitors, the first and second manufacturing methods are described below. According to these manufacturing methods, the electrolytic capacitor of the present invention can be manufactured. Since the matters described for the electrolytic capacitor of the present invention can be applied to the following manufacturing methods, repeated descriptions are sometimes omitted. For example, since the constituent elements of the electrolytic capacitor of the present invention (constituent elements of the anode body, cathode body or cathode layer, separator, and electrolyte layer) have been described above, repeated descriptions are sometimes omitted. Specifically, since the hydroxyl-containing compound (C), conductive polymer, separator, and liquid component (L) have been described above, repeated descriptions are sometimes omitted. In addition, the matters described below can be applied to the above-mentioned electrolytic capacitor of the present invention.
[0067] [First method for manufacturing electrolytic capacitor]
[0068] The first manufacturing method can manufacture the above-mentioned first electrolytic capacitor. The first manufacturing method is a method for manufacturing an electrolytic capacitor including a foil-shaped anode body having a dielectric layer on the surface and a foil-shaped cathode body. The first manufacturing method includes the following steps (i) to (iii).
[0069] (Process (i))
[0070] Step (i) is a step of forming a capacitor element precursor including a separator and a foil-shaped anode body and a foil-shaped cathode body facing each other with the separator interposed therebetween. The capacitor element precursor is a capacitor element before an electrolyte layer is formed.
[0071] The foil-shaped anode body can be formed by a known method. For example, first, a metal foil as a raw material of the anode body is prepared, and the surface of the metal foil is roughened. Roughening can be performed, for example, by etching based on a direct current electrolysis method or an alternating current electrolysis method. Then, a dielectric layer is formed on the surface of the roughened metal foil. The dielectric layer can be formed, for example, by chemically converting the metal foil. The surface of the metal foil is oxidized by chemical conversion treatment of the metal foil, thereby forming a dielectric layer as an oxide film. By operating as described above, the anode body is formed.
[0072] In addition, lead terminals for electrical connection are connected to the anode body and the cathode body as necessary.
[0073] When the first electrolytic capacitor is a wound capacitor, for example, a capacitor element precursor can be formed by winding a foil-shaped anode body, a foil-shaped cathode body, and a separator together. In this case, the anode body and the cathode body are wound so that a separator is disposed between them.
[0074] When the capacitor element is a laminated capacitor, the capacitor element precursor can be formed by, for example, bending a foil-shaped anode body, a foil-shaped cathode body, and a separator together in a zigzag shape. In this case, the anode body and the cathode body are bent so that the separator is disposed between them.
[0075] (Step (ii))
[0076] Step (ii) is a step of placing a hydroxyl-containing compound (hydroxyl-containing compound (C)) having a melting point of 50°C or more, which is at least one compound selected from a group consisting of sugars and polyols, inside the capacitor element precursor. Step (ii) may also be a step of precipitating the hydroxyl-containing compound (C) inside the capacitor element precursor. Therefore, in the following description, "placement" may be replaced by "precipitation".
[0077] Step (ii) includes step (ii-a) and step (ii-b). Step (ii-a) is a step of impregnating the capacitor element precursor with an aqueous treatment liquid containing a hydroxyl group-containing compound (C).
[0078] Step (ii-a) can be performed, for example, by immersing the capacitor element precursor in an aqueous treatment solution. The immersion time is not limited and can be more than 1 minute and less than 20 minutes. The entire capacitor element precursor can be immersed in the aqueous treatment solution, or only a portion of the capacitor element precursor can be immersed in the aqueous treatment solution. For example, only a portion less than 50% of the length direction (axial direction in the case of a winding body) of the capacitor element precursor can be immersed in the aqueous treatment solution.
[0079] Step (ii-a) may be carried out at room temperature or at a temperature other than room temperature (e.g., a temperature higher than room temperature). In addition, step (ii-a) may be carried out at atmospheric pressure or at an environment other than atmospheric pressure (e.g., under reduced pressure).
[0080] The aqueous treatment liquid is a treatment liquid containing water. The amount of water contained in the liquid (solvent) constituting the aqueous treatment liquid is, for example, in the range of 50 to 100% by mass. Usually, the hydroxyl-containing compound (C) is dissolved in the aqueous treatment liquid. That is, the aqueous treatment liquid can be a solution in which the hydroxyl-containing compound (C) is dissolved. In a typical example, the aqueous treatment liquid is an aqueous solution of the hydroxyl-containing compound (C).
[0081] The content (concentration) of the hydroxyl-containing compound (C) in the aqueous treatment liquid (e.g., aqueous solution of the hydroxyl-containing compound (C)) may be in the range of 3 to 50% by mass (e.g., 5 to 15% by mass). The aqueous treatment liquid may contain components other than the hydroxyl-containing compound (C) as required.
[0082] The aqueous treatment liquid may contain a macromolecule (polymer), but preferably does not contain a macromolecule. For example, the aqueous treatment liquid may not contain a conductive macromolecule. The aqueous treatment liquid without a macromolecule has a low viscosity, so it is easy to infiltrate the capacitor element precursor. Here, the so-called macromolecule refers to a polymer with a weight average molecular weight of 1000 or more.
[0083] Step (ii-b) is a step of placing the hydroxyl group-containing compound (C) inside the capacitor element precursor by drying the impregnated aqueous treatment liquid. Step (ii-b) may be performed under atmospheric pressure or under an environment other than atmospheric pressure (eg, under reduced pressure).
[0084] The drying in step (ii-b) is carried out at a prescribed temperature (T). The prescribed temperature (T) is a temperature above the boiling point of the aqueous treatment liquid under the pressure of the drying in step (ii-b) (e.g., above 100°C, above 120°C, above 125°C) and below the melting point of the hydroxy-containing compound (C) under the pressure of the drying in step (ii-b). It should be noted that since the melting point changes little due to pressure, the melting point of the hydroxy-containing compound (C) under 1 atmosphere can be regarded as the melting point of the hydroxy-containing compound (C) under the pressure of the drying in step (ii-b).
[0085] As a result of the study, the inventors of the present application found that, according to the drying conditions of step (ii-b), the hydroxy-containing compound (C) can be biased towards the peripheral portion of the capacitor element precursor compared to the central portion of the capacitor element precursor. Therefore, the hydroxy-containing compound (C) can be biased towards the peripheral portion of the capacitor element manufactured using the manufacturing method. The peripheral portion of the capacitor element is prone to defects in the dielectric layer (oxide film) of the anode body. By configuring the hydroxy-containing compound (C) having multiple hydroxy groups in this portion, it is easy to repair the defects of the dielectric layer. As a result, an electrolytic capacitor with high reliability can be obtained. Specifically, an electrolytic capacitor with a high breakdown voltage and not prone to short circuit can be obtained.
[0086] It should be noted that the step (ii) may be repeated as necessary. By repeating the step (ii), the amount of the precipitated hydroxyl group-containing compound (C) can be increased.
[0087] (Process (iii))
[0088] Step (iii) is a step of forming a conductive polymer layer containing a conductive polymer inside the capacitor element precursor that has undergone step (ii). The conductive polymer layer is a layer that can serve as an electrolyte layer of the first electrolytic capacitor.
[0089] Step (iii) includes step (iii-a) and step (iii-b). Step (iii-a) is a step of impregnating the capacitor element precursor after step (ii) with an aqueous dispersion containing a conductive polymer.
[0090] Step (iii-a) can be performed, for example, by immersing the capacitor element precursor in an aqueous dispersion. The immersion time is not limited and can be more than 1 second and less than 30 minutes. The entire capacitor element precursor can be immersed in the aqueous dispersion, or only a portion of the capacitor element precursor can be immersed in the aqueous dispersion. For example, only a portion less than 50% of the length direction (axial direction in the case of a winding body) of the capacitor element precursor can be immersed in the aqueous dispersion.
[0091] Step (iii-a) may be carried out at room temperature or at a temperature other than room temperature (e.g., a temperature higher than room temperature). In addition, step (iii-a) may be carried out at atmospheric pressure or at an environment other than atmospheric pressure (e.g., under reduced pressure).
[0092] The aqueous dispersion is a treatment liquid containing water. The amount of water contained in the aqueous liquid (dispersion medium) forming the aqueous dispersion is, for example, in the range of 2 to 100% by mass. The aqueous liquid can be water. The conductive polymer is dispersed in the aqueous liquid. That is, the aqueous dispersion is a suspension in which the conductive polymer is dispersed in the aqueous liquid.
[0093] The content (concentration) of the conductive polymer in the aqueous dispersion may be in the range of 0.1 to 20% by mass (eg, in the range of 0.5 to 3% by mass).
[0094] The viscosity of the aqueous dispersion may be in the range of 1 mPa·s to 100 mPa·s, or in the range of 1 mPa·s to 40 mPa·s (eg, 1 mPa·s to 25 mPa·s). The lower the viscosity of the aqueous dispersion, the easier it is to impregnate the capacitor element precursor.
[0095] The aqueous dispersion preferably does not contain the above-mentioned hydroxyl-containing compound (C). By not adding the hydroxyl-containing compound (C), the viscosity of the aqueous dispersion can be reduced. Even if the aqueous dispersion contains a hydroxyl-containing compound (C), it is preferred that the hydroxyl-containing compound (C) is contained within a range where the viscosity of the aqueous dispersion is below a certain value (e.g., below 40 mPa·s, below 25 mPa·s).
[0096] As described above, a dopant may be added to the conductive polymer. In addition, the aqueous dispersion may contain components other than the conductive polymer and the dopant as necessary.
[0097] Step (iii-b) is a step of drying the impregnated aqueous dispersion to form a conductive polymer layer. Typically, the conductive polymer layer contains a conductive polymer as a main component.
[0098] The method for drying the aqueous dispersion is not particularly limited. Step (iii-b) can be carried out under atmospheric pressure or under an environment other than atmospheric pressure (e.g., under reduced pressure). In step (iii-b), at least heating is usually performed. The heating temperature in step (iii-b) can satisfy the following conditions (1) and / or (2).
[0099] (1) The heating temperature in step (iii-b) is a temperature not less than the boiling point of the aqueous dispersion under the pressure of drying in step (iii-b) and less than the melting point of the hydroxyl group-containing compound (C) under the pressure of drying in step (iii-b).
[0100] (2) The heating temperature in step (iii-b) is higher than the heating temperature in step (ii-b).
[0101] In order to achieve high characteristics (such as low ESR), it is necessary to increase the content of the conductive polymer in the electrolyte layer. For this reason, it is important to improve the fixation of the conductive polymer. As one of the methods for improving the fixation of the conductive polymer, it is conceivable to add polyols to the aqueous dispersion of the conductive polymer. However, if polyols are added to the aqueous dispersion, the viscosity of the aqueous dispersion increases, thereby causing the problem that the infiltration of the aqueous dispersion becomes difficult. In the manufacturing method of the present invention, first, after being treated with an aqueous treatment solution containing a hydroxyl-containing compound (C), the aqueous dispersion is infiltrated. Therefore, the infiltration of the aqueous dispersion is easy. In addition, by pre-arranging the hydroxyl-containing compound (C) in the capacitor element precursor, the conductive polymer infiltrated thereafter can be firmly fixed. As a result, an electrolytic capacitor with high characteristics can be manufactured.
[0102] The electrolyte layer is formed by the above operation. That is, the capacitor element including the electrolyte layer is formed by the above operation.
[0103] The capacitor element obtained as described above can be used to manufacture the electrolytic capacitor (first and second electrolytic capacitors) of the present invention. The method of manufacturing an electrolytic capacitor using a capacitor element is not particularly limited, and a known method can be applied. For example, the capacitor element can be placed in a housing and sealed.
[0104] [Second Method for Manufacturing Electrolytic Capacitor]
[0105] The second manufacturing method can manufacture the above-mentioned second electrolytic capacitor. The second manufacturing method is a method for manufacturing an electrolytic capacitor including a porous anode body having a dielectric layer on its surface. The second manufacturing method includes step (I) and step (II).
[0106] (Step (I))
[0107] Step (I) is a step of placing a hydroxyl-containing compound (C) having a melting point of 50° C. or higher, which is at least one compound selected from the group consisting of sugars and polyols, on the surface of the anode body. The anode body described in the second electrolytic capacitor can be used as a porous anode body having a dielectric layer on the surface.
[0108] Step (I) includes step (Ia) and step (Ib). Step (Ia) is a step of impregnating an aqueous treatment solution containing a hydroxyl-containing compound (C) into an anode body. Step (Ia) can be performed under the same conditions as step (ii-a), except that the anode body is used instead of a capacitor element precursor. For example, the aqueous treatment solution described in step (ii-a) can be used as the aqueous treatment solution.
[0109] Step (Ib) is a step of placing the hydroxyl-containing compound (C) on the surface of the anode body by drying the impregnated aqueous treatment liquid. The drying in step (Ib) is performed at a predetermined temperature. The predetermined temperature is a temperature above the boiling point of the aqueous treatment liquid under the pressure at which the drying in step (Ib) is performed and a temperature below the melting point of the hydroxyl-containing compound (C) under the pressure at which the drying in step (Ib) is performed. The drying in step (Ib) can be performed under the same conditions as the drying described in step (ii-b).
[0110] (Step (II))
[0111] Step (II) is a step of forming a conductive polymer layer containing a conductive polymer on the anode body (on the dielectric layer of the anode body) that has undergone step (I).
[0112] Step (II) includes step (II-a) and step (II-b). Step (II-a) is a step of impregnating an aqueous dispersion containing a conductive polymer into the anode body after step (I). Step (II-a) can be performed under the same conditions as step (iii-a), except that the anode body is used instead of the capacitor element precursor. For example, the aqueous dispersion described in step (iii-a) can be used as the aqueous dispersion.
[0113] When the conductive polymer is dispersed in the dispersion medium in the form of particles, the average particle size of the particles may be in the range of 0.1 μm to 0.5 μm. If the average particle size of the particles is in this range, the particles are easy to penetrate into the interior of the anode body. Here, the average particle size is the median particle size (D 50 ). The median particle size is determined, for example, using a laser diffraction / scattering particle size distribution measuring apparatus.
[0114] Step (II-b) is a step of forming a conductive polymer layer on the anode body by drying the impregnated aqueous dispersion. The drying in step (II-b) can be performed under the same conditions as the drying described in step (iii-b). For example, the heating temperature in step (II-b) can satisfy the following (1) and / or (2).
[0115] (1) The heating temperature in step (II-b) is a temperature not less than the boiling point of the aqueous dispersion under the pressure of drying in step (II-b) and less than the melting point of the hydroxyl group-containing compound (C) under the pressure of drying in step (II-b).
[0116] (2) The heating temperature in step (II-b) is higher than the heating temperature in step (Ib).
[0117] By operating as described above, a conductive polymer layer (electrolyte layer) formed on the anode body (on the dielectric layer) is obtained. Thereafter, a cathode layer is formed on the conductive polymer layer (electrolyte layer). The cathode layer can be formed, for example, by coating the material constituting the cathode layer on the electrolyte layer. By operating as described above, a capacitor element is obtained. The capacitor element can be used to manufacture an electrolytic capacitor (a second electrolytic capacitor). The method for manufacturing an electrolytic capacitor using a capacitor element is not particularly limited, and a known method can be applied.
[0118] Hereinafter, an example of the electrolytic capacitor of the present invention will be specifically described with reference to the accompanying drawings, however, the electrolytic capacitor of the present invention is not limited to the following drawings. The above-mentioned constituent elements can be applied as constituent elements of an electrolytic capacitor of an example described below. In addition, the constituent elements of an electrolytic capacitor of an example described below can be changed based on the above description. In addition, the matters described below can also be applied to the above-mentioned embodiment. It should be noted that sometimes the same symbols are used for the same parts and repeated descriptions are omitted.
[0119] (Implementation Method 1)
[0120] In the first embodiment, an example of a first electrolytic capacitor is described. Figure 1 A cross section of an example of electrolytic capacitor 100 according to Embodiment 1 is schematically shown. Figure 2 Indicates that Figure 1 FIG. 1 is a schematic diagram showing a portion of a capacitor element included in an electrolytic capacitor 100 that is expanded.
[0121] like Figure 1As shown, the electrolytic capacitor 100 includes, for example, a capacitor element 10, a bottomed casing 11 for accommodating the capacitor element 10, a sealing member 12 for sealing the opening of the bottomed casing 11, a seat plate 13 covering the sealing member 12, leads 14A and 14B extending from the sealing member 12 and passing through the seat plate 13, and lead connectors 15A and 15B (not shown) for connecting the leads 14A and 14B to electrodes of the capacitor element 10. The capacitor element 10 is accommodated in the bottomed casing 11. In the case where the capacitor element 10 contains a liquid component (L), the liquid component (L) is also accommodated in the bottomed casing 11. The opening end of the bottomed casing 11 is necked inwardly, and the opening end is crimped in a manner of being riveted to the sealing body 12.
[0122] The capacitor element 10 includes an anode body 21 having a dielectric layer on the surface, a cathode body 22, and a separator 23 disposed therebetween. They form an electrode group (wound body) 20. The capacitor element 10 includes an electrolyte layer (not shown) disposed between the anode body 21 and the cathode body 22. The anode body 21 and the cathode body 22 are wound with the separator 23 disposed therebetween. The outermost periphery of the wound body is fixed by a winding fixing tape 24. It should be noted that Figure 2 The diagram shows a partially unwound state before the outermost circumference of the wound body is fixed.
[0123] The electrolyte layer has localized portions where the hydroxyl group-containing compound (C) is localized at both end portions of the wound body in the winding axis direction and at the outermost peripheral portion of the wound body.
[0124] (Implementation Method 2)
[0125] In the second embodiment, an example of a capacitor element included in the second electrolytic capacitor will be described. Figure 3 A cross section of capacitor element 210 of the electrolytic capacitor according to Embodiment 2 is schematically shown.
[0126] The capacitor element 210 includes an anode portion 220 and a cathode portion 230. The anode portion 220 includes an anode body 221 and an anode wire 222. The anode body 221 includes a dielectric layer 221a formed on the surface. A portion of the anode wire 222 is buried in the anode body 221. The cathode portion 230 has an electrolyte layer (e.g., a solid electrolyte layer) 231 covering at least a portion of the dielectric layer 221a and a cathode layer 232 covering the electrolyte layer 231.
[0127] The anode wire 222 is formed of a conductive material. The material of the anode wire 222 is not particularly limited, and may be the above-mentioned valve-acting metal or other metals (copper, aluminum, aluminum alloy, etc.).
[0128] In one example of the production of the anode portion 220, first, a portion of the anode wire 222 is buried in a metal powder (raw material of the anode body 221) and the powder is pressurized into a rectangular parallelepiped. Then, the powder is sintered. By operating as described above, the anode body 221 before the dielectric layer 221a is formed is obtained. The method for forming the dielectric layer 221a is not limited, and it can be formed using a known method. The dielectric layer 221a can be formed by immersing the anode body 221 in a chemical solution and anodizing the surface of the anode body 221. Alternatively, the dielectric layer 221a can also be formed by heating the anode body 221 in an atmosphere containing oxygen.
[0129] The method of forming the electrolyte layer 231 and the cathode layer 232 is not limited, and they can be formed by the above-mentioned method or a known method.
[0130] Capacitor element 210 may be connected with lead wires or sealed with an insulating material (eg, insulating resin) as required. These are not limited, and known techniques may be applied. In this manner, a second electrolytic capacitor is obtained.
[0131] Example
[0132] Hereinafter, the embodiments of the present invention will be described in further detail using examples. In this example, a plurality of electrolytic capacitors (capacitors A1, A2 and capacitors C1 to C4) are manufactured and evaluated. The manufacturing method and evaluation method of these capacitors are described as follows. It should be noted that in the description of the manufacturing method of the capacitor of the comparative example, conditions different from those of the above-mentioned steps (ii) and (iii) are sometimes used, but for convenience, they are also described as steps (ii) and (iii).
[0133] [Fabrication of capacitor A1]
[0134] Capacitor A1 is a wound electrolytic capacitor (diameter 10 mm×length 10 mm) having a rated voltage of 35 V and a rated electrostatic capacitance of 270 μF. Capacitor A1 was produced by the following steps.
[0135] (Preparation of cathode body)
[0136] As the cathode body, an Al foil (aluminum foil) having a thickness of 50 μm was used.
[0137] (Preparation of anode body)
[0138] Prepare an Al foil with a thickness of 120 μm. Perform a DC etching treatment on the Al foil to roughen the surface. Then, perform a chemical conversion treatment on the Al foil to form a dielectric layer (thickness: about 70 nm), thereby obtaining an anode body. Immerse the Al foil in an ammonium adipate solution, apply a voltage of 50 V to the Al foil, and perform a chemical conversion treatment at 70°C for 5 hours to form a dielectric layer. Thereafter, cut the anode body into a specified size, thereby preparing the anode body of capacitor A1.
[0139] (Production of wound body (step (i)))
[0140] An anode lead connector and a cathode lead connector connected to leads are connected to the prepared anode body and cathode body, respectively. Thereafter, the anode body and the cathode body are wound with a separator sandwiched therebetween, and the outer surfaces are fixed with a winding fixing tape. A non-woven fabric made of aramid (aromatic polyamide fiber), which is a synthetic fiber, is used as a separator. A wound body (capacitor element precursor) is produced by operating as described above. The produced wound body is immersed in an ammonium adipate solution, and while applying a voltage of 50 V to the anode body, a chemical conversion treatment is performed again at 70°C for 60 minutes, thereby forming a dielectric layer mainly on the end face of the anode body.
[0141] (Preparation of aqueous treatment solution)
[0142] Mannitol was dissolved in ion-exchanged water to prepare a mannitol aqueous solution having a concentration of 10% by mass. The viscosity of the obtained mannitol aqueous solution was measured to be 5 mPa·s or less.
[0143] (Preparation of aqueous dispersion)
[0144] A mixed solution of 3,4-ethylenedioxythiophene and polystyrene sulfonic acid as a dopant is prepared by dissolving them in ion exchange water. While stirring the obtained mixed solution, iron (III) sulfate (oxidant) dissolved in ion exchange water is added to carry out a polymerization reaction. After the reaction, the obtained reaction solution is dialyzed to remove unreacted monomers and excess oxidant, thereby obtaining a dispersion (aqueous dispersion) containing poly(3,4-ethylenedioxythiophene) doped with about 5% by mass of polystyrene sulfonic acid (PSS). Hereinafter, poly(3,4-ethylenedioxythiophene) doped with about 5% by mass of polystyrene sulfonic acid (PSS) is sometimes referred to as "PEDOT:PSS". In addition, a dispersion in which PEDOT:PSS is dispersed is sometimes referred to as "PEDOT:PSS dispersion". Using this PEDOT:PSS dispersion, an aqueous dispersion having a PEDOT:PSS concentration of 2% by mass is prepared. The viscosity of the obtained dispersion was measured, and the result was 25 mPa·s.
[0145] (Step (ii))
[0146] First, an aqueous treatment liquid is placed in a container. Then, at room temperature and atmospheric pressure, the wound body (capacitor element precursor) is immersed in the aqueous treatment liquid in the container for 5 minutes. At this time, the wound body is immersed in the aqueous treatment liquid from the side to which the lead connector is not connected (the same is true in the other immersion steps described below). Thereafter, the wound body is lifted from the aqueous treatment liquid. The operation is performed as described above to allow the aqueous treatment liquid to penetrate into the wound body. Then, the wound body is dried at 125°C for 30 minutes in a drying furnace at a pressure of 1 atmosphere, thereby drying the aqueous treatment liquid. The operation is performed as described above to configure mannitol as a hydroxyl-containing compound (C) inside the wound body.
[0147] In addition, when the wound body was unfolded and the electrolyte layer was observed, it was found that mannitol was precipitated in the locations corresponding to the two ends of the wound body in the axial direction and the location corresponding to the outermost circumference of the wound body. That is, for the electrolyte layer, there were locations where mannitol was precipitated in the two ends of the wound body in the winding axis direction and the outermost circumference of the wound body.
[0148] (Process (iii))
[0149] First, an aqueous dispersion is placed in a container. Then, at room temperature and under a reduced pressure atmosphere (40 kPa), the wound body is immersed in the aqueous dispersion in the container for 15 minutes, and thereafter, the wound body is lifted from the aqueous dispersion. The wound body is impregnated with the aqueous dispersion by the above operation. Then, the wound body is dried at 150° C. for 30 minutes in a drying furnace at a pressure of 1 atmosphere. Thus, the aqueous dispersion is dried. The above operation forms a conductive polymer layer.
[0150] (Impermeation of electrolyte)
[0151] The wound body that has undergone step (iii) is impregnated with an electrolyte at room temperature and atmospheric pressure. A solution in which polyethylene glycol, γ-butyrolactone, cyclopentane sulfone and mono(ethyldimethylamine)phthalate (solute) are mixed in a mass ratio of polyethylene glycol: γ-butyrolactone: cyclopentane sulfone: mono(ethyldimethylamine)phthalate = 25:25:25:25 is used as the electrolyte. By operating as described, a capacitor element including an electrolyte layer is obtained. The capacitor element is sealed to complete an electrolytic capacitor. Thereafter, an aging treatment is performed at 130°C for 2 hours while applying the rated voltage. By operating as described, capacitor A1 is obtained.
[0152] [Capacitor A2]
[0153] Capacitor A2 was produced under the same conditions as capacitor A1 except that the spacer was changed. Cellulose-based natural fibers were used as the spacer.
[0154] [Capacitor C1]
[0155] The capacitor C1 was produced under the same conditions as those of the capacitor A1 except that the step (ii) was not performed and the conditions of the step (iii) were changed.
[0156] In step (iii) of capacitor C1, mannitol was dissolved in the PEDOT:PSS dispersion described in the preparation of capacitor A1 to prepare an aqueous dispersion. The concentration of PEDOT:PSS in the aqueous dispersion was set to 2% by mass, and the concentration of mannitol was set to 10% by mass. The viscosity of the obtained dispersion was measured and found to be 45 mPa·s.
[0157] The aqueous dispersion was used for impregnation under the same conditions as in step (iii) of capacitor A1. Then, the wound body was dried in a drying oven at 60°C for 30 minutes and then at 125°C for 15 minutes. The aqueous dispersion was dried. In this way, a conductive polymer layer was formed. Thereafter, capacitor C1 was produced using the same process as capacitor A1.
[0158] [Capacitor C2]
[0159] Capacitor C2 was produced under the same conditions as capacitor A1 except that the drying temperature in step (ii) and the drying temperature and time in step (iii) were changed.
[0160] In the step (ii) of the capacitor C2, drying was performed at 180° C. for 30 minutes. In the step (iii) of the capacitor C2, drying was performed at 60° C. for 30 minutes, and then at 125° C. for 15 minutes.
[0161] [Capacitor C3]
[0162] Capacitor C3 was produced under the same conditions as capacitor C2 except that step (ii) was not performed.
[0163] [Capacitor C4]
[0164] Capacitor C4 was produced under the same conditions as capacitor C2 except that the spacer was changed. Cellulose-based natural fibers were used as the spacer.
[0165] (Evaluation of distribution of mannitol)
[0166] The wound body (capacitor element precursor before step (ii)) produced in step (i) of capacitor A1 was visually observed for the axial end face of the wound body. A photograph of the end face is shown in FIG. Figure 4(a). In addition, for capacitor A1 and capacitor C2, the end faces of the winding bodies after the step (ii) were visually observed. Photos of these end faces are shown in Figure 4 (b) and Figure 4 (c). Figure 4 As shown, when the capacitor A1 was subjected to step (ii), mannitol was concentrated in a white manner on the end surface of the winding body. The precipitated portion existed at both ends of the winding body. On the other hand, after step (ii) of the capacitor C2, such concentration was not observed.
[0167] Then, the three winding bodies were disassembled and the electrolyte held in the separator was observed. In the electrolyte after the step (ii) of the capacitor A1, mannitol was concentrated in the parts corresponding to the two ends of the winding body in the winding axis direction and the part corresponding to the outermost circumference of the winding body. On the other hand, in the electrolyte after the step (ii) of the capacitor C2, no such concentration was observed.
[0168] The same method as the above-mentioned method for making each capacitor is used until step (ii). Thereafter, the wound body (capacitor element precursor) that has undergone step (ii) is decomposed to study the distribution of mannitol in the electrolyte layer. Specifically, the identification of mannitol is implemented using a microscopic FT-IR analyzer (Nicolet-iN10 manufactured by ThermoFisher). For the distribution ratio of mannitol, first, the end of the capacitor element and the central part of the capacitor element are cut out, and the mannitol attached to each part is extracted with an aqueous solvent. Then, the dry weight of mannitol present in each part is calculated. The distribution ratio of mannitol is calculated based on the dry weight. Similarly, the same method as the above-mentioned method for making each capacitor is used until step (iii) to calculate the distribution ratio of mannitol in the electrolyte layer.
[0169] (Evaluation of characteristics)
[0170] The equivalent series resistance (ESR) of the electrolytic capacitor produced as described above was measured. The ESR was measured using a 4-terminal LCR tester at 20°C. In addition, a voltage was applied to the electrolytic capacitor while increasing the voltage at a rate of 1.0 V / sec, and the breakdown voltage with an overcurrent of 0.5 A was measured.
[0171] Thirty capacitors of each of the six types were prepared, and a rated voltage of 35 V was applied in an environment of 150° C. to check whether a short circuit occurred after 60 minutes. Thereafter, the number of capacitors short-circuited among the 30 capacitors was evaluated.
[0172] The measurement results and part of the production conditions of the electrolytic capacitor are shown in Table 1. In Table 1, the term "PEDOT:PSS mixture" means that the aqueous dispersion contains PEDOT:PSS and mannitol.
[0173]
[0174] The drying temperature of step (ii-b) of capacitors A1 and A2 is above the boiling point of the aqueous treatment liquid. In addition, the melting point of mannitol is about 165 to 169°C. Therefore, the drying temperature of step (ii-b) of capacitors A1 and A2 is above the boiling point of the aqueous treatment liquid and below the melting point of mannitol (hydroxyl-containing compound (C)). On the other hand, the drying temperature of step (ii-b) of capacitors C2 and C4 is higher than the melting point of mannitol (hydroxyl-containing compound (C)).
[0175] The ESR value is preferably low. The ESR value is preferably 20 mΩ or less (e.g., in the range of 3 to 20 mΩ), and more preferably 12 mΩ or less (e.g., in the range of 3 to 12 mΩ). The breakdown voltage is preferably high, preferably 75 V or more (e.g., in the range of 75 to 100 V). The number of short circuits is preferably small.
[0176] As shown in Table 1, for capacitors A1 and A2 of the present invention, ESR, breakdown voltage and number of short circuits are all good. The low ESR is believed to be due to the electrolyte layer containing mannitol (hydroxyl-containing compound (C)). The low breakdown voltage and number of short circuits are believed to be due to the presence of mannitol at both ends of the winding body in the winding axis direction and the outermost periphery of the winding body.
[0177] Comparing capacitor C2 using a synthetic fiber spacer with capacitor C3 using a natural fiber spacer, the breakdown voltage and the number of short circuits in capacitor C3 using a natural fiber spacer are significantly worse. On the other hand, there is no significant difference between capacitor A1 and capacitor A2. This is believed to be because the spacer is strengthened by performing step (ii).
[0178] Industrial Applicability
[0179] The present invention can be applied to an electrolytic capacitor and a method for manufacturing the same.
[0180] Description of Reference Numerals
[0181] 10, 210 capacitor element, 20 electrode group, 21, 221 anode body, 22 cathode body, 23 separator, 100 electrolytic capacitor, 221a dielectric layer, 222 anode wire, 230 cathode part, 231 electrolyte layer, 232 cathode layer.
Claims
1. A method for manufacturing an electrolytic capacitor, A method for manufacturing an electrolytic capacitor including a foil-shaped anode body having a dielectric layer on the surface and a foil-shaped cathode body. It includes: Step (i) of forming a capacitor element precursor by winding or stacking a separator, the anode body and the cathode body facing each other with the separator interposed therebetween; Step (ii), placing a hydroxyl group-containing compound having a melting point of 50° C. or higher, which is at least one compound selected from the group consisting of sugars and polyols, inside the capacitor element precursor; as well as step (iii) of forming a conductive polymer layer containing a conductive polymer inside the capacitor element precursor after the step (ii), The step (ii) comprises: Step (ii-a), impregnating the capacitor element precursor with an aqueous treatment liquid containing the hydroxyl group-containing compound; and Step (ii-b), placing the hydroxyl group-containing compound inside the capacitor element precursor by drying the impregnated aqueous treatment liquid, The step (iii) comprises: step (iii-a), impregnating the capacitor element precursor having undergone the step (ii) with an aqueous dispersion containing the conductive polymer; and step (iii-b), forming the conductive polymer layer by drying the impregnated aqueous dispersion, The drying in the step (ii-b) is performed at a predetermined temperature. The predetermined temperature is a temperature not less than the boiling point of the aqueous treatment liquid under the pressure at which the drying in the step (ii-b) is performed and is a temperature less than the melting point of the hydroxyl-containing compound under the pressure at which the drying in the step (ii-b) is performed. The hydroxyl-containing compound is at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol and trimethylolpropane.
2. A method for manufacturing an electrolytic capacitor, A method for manufacturing an electrolytic capacitor including a porous anode body having a dielectric layer on the surface. It includes: Step (I), placing a hydroxyl group-containing compound having a melting point of 50° C. or higher, which is at least one compound selected from the group consisting of sugars and polyols, on the surface of the anode body; and Step (II) of forming a conductive polymer layer containing a conductive polymer on the anode body having undergone the step (I), The step (I) comprises: Step (Ia), impregnating the anode body with an aqueous treatment solution containing the hydroxyl-containing compound; and Step (Ib) of placing the hydroxyl-containing compound on the surface of the anode body by drying the impregnated aqueous treatment liquid, The step (II) comprises: step (II-a), impregnating the anode body having undergone the step (I) with an aqueous dispersion containing a conductive polymer; and Step (II-b) of forming the conductive polymer layer on the anode body by drying the impregnated aqueous dispersion. The drying in step (Ib) is performed at a predetermined temperature. The predetermined temperature is a temperature not less than the boiling point of the aqueous treatment liquid at the pressure at which the drying in the step (Ib) is performed and is a temperature less than the melting point of the hydroxyl-containing compound at the pressure at which the drying in the step (Ib) is performed. The hydroxyl-containing compound is at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol and trimethylolpropane.
3. The manufacturing method according to claim 1 or 2, wherein: The viscosity of the aqueous dispersion is in the range of 1 Pa·s to 100 Pa·s.
4. The manufacturing method according to claim 1 or 2, wherein: The aqueous treatment liquid does not contain polymers.
5. The manufacturing method according to claim 1 or 2, wherein: The conductive polymer is poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid.
6. An electrolytic capacitor, It is an electrolytic capacitor containing capacitor elements, The capacitor element comprises: An electrode group including a foil-shaped anode body having a dielectric layer on its surface, a foil-shaped cathode body, and a separator; and an electrolyte layer in contact with the anode body, the cathode body and the separator, The electrode group is a wound body formed by winding the anode body and the cathode body facing each other with the separator interposed therebetween, or a stacked body formed by stacking the anode body and the cathode body facing each other with the separator interposed therebetween, The electrolyte layer comprises a conductive polymer and a hydroxyl-containing compound having a melting point of 50° C. or higher, which is at least one compound selected from the group consisting of sugars and polyols. The hydroxyl-containing compound is located at a peripheral portion of the capacitor element rather than a central portion of the capacitor element. The hydroxyl-containing compound is at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol and trimethylolpropane.
7. The electrolytic capacitor according to claim 6, wherein: The electrode group is the wound body, The electrolyte layer has localized portions where the hydroxyl-containing compound is localized at both end portions of the wound body in the winding axis direction and at the outermost peripheral portion of the wound body.
8. The electrolytic capacitor according to claim 6, wherein: The electrode group is the stacked body, The electrolyte layer has a localized portion where the hydroxyl-containing compound is localized in a portion in contact with the peripheral edge portion of the anode body.
9. The electrolytic capacitor according to any one of claims 6 to 8, wherein: The electrolyte layer contains a non-aqueous solvent or a non-aqueous electrolyte solution.
10. An electrolytic capacitor, It is an electrolytic capacitor containing capacitor elements, The capacitor element includes a porous anode body having a dielectric layer on its surface, a cathode layer, and an electrolyte layer disposed between the anode body and the cathode layer. The capacitor element contains a conductive polymer and a hydroxyl-containing compound having a melting point of 50° C. or higher, which is at least one compound selected from the group consisting of sugars and polyols. The hydroxyl-containing compound is located at the peripheral portion of the anode body rather than the central portion of the anode body. The hydroxyl-containing compound is at least one selected from the group consisting of glucose, mannitol, sorbitol, xylitol, pentaerythritol and trimethylolpropane.
11. The electrolytic capacitor according to claim 6 or 10, wherein: The conductive polymer is poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonic acid.
Citation Information
Patent Citations
Electrolytic-capacitor and manufacturing method therefor
JP2008010657A
Solid electrolytic capacitor containing a protective adhesive layer
CN101271770A
Electrically conductive polymer solution, electrically conductive polymer material and process for production thereof, and solid electrolytic capacitor
CN103459495A
Manufacturing method of solid state electrolytic capacitor
JP2013138145A